Play-based Andragogy through 3D Jigsaw Puzzle: Enhancing Social Engagement and Collaborative Descriptive Writing - Eka Putri, Rahmadila (Tarbiyah : Jurnal Ilmiah Kependidikan, 2025)
Play-based approach, traditionally reserved for childhood education, has demonstrated substantial potential in emerging adulthood learning, aiding in the cultivation of creativity, critical thinking, and interpersonal communication. This study investigates the efficacy of play-based approach, through 3D jigsaw puzzles, in fostering social interaction and collaborative descriptive writing within andragogy setting. Grounded in experiential and student-centred learning theories, it aligns with the developmental needs of young adults, promoting engagement and holistic growth. The study aimed to explore students’ perceptions of play-based approach and identify patterns of social interaction during collaborative descriptive writing. Conducted at regional branch campus of State Polytechnic of Sriwijaya, this study utilized convenience sampling for one small class consisted with nine freshmens. A mixed-method design was employed through closed-ended questionnaire and non-participative observation to provide a comprehensive analysis. The findings demonstrated that play-based approach enhanced engagement, mitigated stress, and nurtured partnerships through peer support, role specialization, and joint problem-solving which was exerting a positive influence on descriptive writing outcomes. Ultimately, the study suggests that play-based approach can profoundly amplify emerging adulthood education, particularly in collaborative learning. Therefore, this approach could feasibly serve as a constructive foundation for the development of future andragogy curricula.